THEORETICAL STUDIES ON THE PROCESS OF CHANGE OF THE TECHNICAL CONDITION OF FREIGHT CARS IN OPERATION - V. Y. Shaposhnyk (Nauka ta progres transportu, 2018)
Purpose. The scientific work is intended to investigate the technical condition of freight cars during their operation. The said purpose involves solving the following tasks: 1) to describe the technical condition of a freight car during the maintenance and repair period; 2) to determine the dependences of the probability of a freight car being in working condition during the life cycle; 3) to specify the expression for the technical availability ratio of the car fleet. Methodology. To achieve the purpose, the author examined the methodological approaches to the definition of various stages of the freight car life cycle. The system of change and transition of the technical condition of the freight car is described using differential equations. Findings. In the case of an unstable process of changing the technical condition of a freight car, the probabilistic characteristic of the appropriate life cycle stage depends on the amount of time. The intensity of the input and output flows are correlated with each other, taking into account the probability of a freight car being at the appropriate stage of its life cycle. Originality. Transitions from one car life cycle to another occur in discrete steps, that is, such transitions are characterized by a random process. The probability of a freight car being at the appropriate life cycle is determined by its prior technical condition. The total value of the set of all possible conditions consists of the Markov chain for random processes with random states and a continuous flow of time. The study resulted in obtaining, for the first time, of the dependence of the probability of a freight car being in working condition during the life cycle. Practical value. On the basis of the obtained definition for the probability of the freight car being in working condition the expression for the technical availability ratio of the car fleet was clarified.